Niche evolution reveals disparate signatures of speciation in the 'great speciator' (white‐eyes, Aves: Zosterops). (8th May 2021) - Engler, Jan O.; Lawrie, Yvonne; Cabral, Juliano S.; Lens, Luc; Martínez‐Meyer, Enrique
Abstract: Aim: Recent breakthroughs in environmental niche models (ENMs) have substantially improved our insights in niche evolution. Assuming that closely related taxa have similar niches (i.e. niche conservatism), the combination of ENMs with phylogenetic information allows the reconstruction of ancestral niches. This reconstruction helps to identify the underlying speciation processes leading to diversification (i.e. ecological speciation under niche divergence and mutation‐order speciation under niche conservatism). Here, we studied the niche evolution in white‐eyes (the so‐called 'great speciator') to understand their extraordinarily fast diversification rate, wide distribution and rather conserved phenotypes. In a broader perspective, unravelling niche evolution in white‐eyes can shed light on how different niche properties such as climate, habitat or trophic level may contribute to diversification. Location: Asian‐Pacific and Afrotropics. Taxon: White‐eyes (Aves, genus: Zosterops ). Methods: We selected 10 wide‐ranging taxa that are equally distributed across the genus' range and phylogeny. We studied niche evolution for a series of thermal and precipitation‐related niche axes separately. We used a time‐calibrated phylogeny encompassing the study taxa and estimated ancestral environmental niches in geographic and environmental niche spaces. Results: We found that niche evolution in Zosterops is primarily driven by ecological speciation. Thermal niches, in particular, are characterized by a higher level of conservatism, as compared to precipitation‐related niche axes. The fact that the youngest species diverged strongest stands in stark contrast to expectations stemming from niche conservatism. Main conclusions: Contrasting evolutionary patterns in different niche axes suggest different underlying evolutionary pressures. Hence, future studies on niche evolution should take possible disparities between niche axes into account.